(untitled) (Fiep Bulletin - online, 2013)
The swimming stands out as an excellent way to improve the physical condition. Although the intense and repetitive movements may cause osteomuscular unbalance. Considering the principle of biological individuality and the fact that physical exercises aim to maintain health, this study is proposed to check the occurrence of osteomuscular unbalance in the shoulder complex of practicing swimming, confronting the etiology of these disorders with some flaws in the implementation of biomechanics swimming crawl. There was a sample of three women with ages averaging 23 ± 4,58 and seven men averaging 24 ± 6,92, with at least 6 months of practice three ice a week, enrolled in clubs and gyms of Montes Claros. These individuals were subjected to posture assessment, tests on muscle length, evidence of muscle function and evaluation of the technique of swimming. The results revealed that there is significative occurrence of osteomuscular unbalance in the shoulder complex of swimmers with postural changes such as forward positioning of the anteriorization on humerus head in (100%) of individuals, depressed shoulders and humerus internal rotation (80%) and inferior rotation of scapula (50%), besides the changes on function as weakness, (90%) with posterior deltoid muscle weakness, lateral rotators of shoulder (70%), lift the scapula and rhomboid (80%) and inferior trapezium at 100% Of the cases, and muscle in length, (50%) with muscular length from the major dorsal muscles, intern rotators of shoulders and minor chest (60%) with strengthen of the external rotators. The results of the study and literature can say that the correct technique does not guarantee the accuracy of imbalances, but it is a preventive aspect when combined with a previous assessment and correction of certain changes or inappropriate posture habits.